Pembuatan Biodiesel Dari Minyak Biji Karet Menggunakan Reaktor Membran - Fauzi, Subehan; Syarfi, Syarfi; Bahruddin, Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
One of the challenges in biodiesel manufacturing were the limited conventional mass transfer. The problem can be solved by using new technology in the biodiesel manufacturing process, namely tmembrane reactor. Membrane reactor has a close relationship to productivity and selectivity. This research aims to study the effect of variations in the molar ratio and transmembrane pressure on the characteristics and productivity of biodiesel. This research was conducted by two stages of preparation of rubber seed oil and biodiesel production using a membrane reactor. Rubber seed oil preparation process consists of stripping, drying, resizing, extraction and degumming. Biodiesel production is conducted by using H2SO4 catalyst, reaction time 6 h, reaction temperature 60°C, the variation of the molar ratio of 1:15, 1:20 and 1:25 and transmembrane pressure of 1 bar, 1.5 bar and 2 bar. Results of preparation of rubber seed oil yield of 19% was obtained with a free fatty acid content before and after degumming is 37.6% and 29.12%. The results showed the highest yield of biodiesel production amounted to 62.15% at a molar ratio of 1:20 and a transmembrane pressure of 1.5 bar. Biodiesel produced has a density of 0.880 g/ml, viscosity 7.73 mm2/s and flash point 180oC. The largest composition of biodiesel ie 26.5% of Oleic Acid Methyl Ester.Keywords: biodiesel, membrane reactor, rubber seed oil